Conjugating Existing Clinical Drugs With Gold Nanoparticles for Better Treatment of Heart Diseases - Zhang, Jingwen; Ma, Aiqun; Shang, Lijun (Frontiers in Physiology, 2018)
Cardiovascular disease is a major illness across the world. Although some clinical drugs are available, the strong side-effects and life-long time administration of the drugs remain to be concerns. Recent use of nanoparticles (NPs) in treating atherosclerosis in animals and some other heart diseases such as heart failure and endocarditis have provided hopes for better drug delivery and reducing of drug side-effects. In this review, we summarised the present applications of using gold nanoparticles (GNPs) as a new drug delivery system in diseased hearts and discussed the assessment of toxicity of using GNPs. We suggested that conjugating clinical “old” drugs with GNPs is a favorable choice to provide “new and double-enhanced” potentiality to those “old” drugs to treat heart diseases. Other applications of using NPs in the treatment of heart diseases including using drugs in nano-form and coating drugs with a surface of relevant nanoparticle were also discussed.